Pemanfaatan Lahan Pekarangan Untuk Pertanian dan Perikanan Dalam Menunjang Ketahanan Pangan Rumah Tangga Masyarakat di Kelurahan Bungkutoko Kecamatan Nambo Kota Kendari - Iswandi, R. Marsuki; Alwi, La Ode; Nikoyan, Anas; Fyka, Samsul Alam (Vokasi Universitas Halu Oleo, 2020)
The problem that occurs at the community service location is the plot of land which is still not optimally utilized to support the availability of household food from agricultural and fishery foods. The purpose of this community service program is to increase public knowledge and awareness of the importance of using yard space in support of household food availability, in addition to practicing how to use simple plot land in the form of aquaponics to meet the availability of vegetable and fish food as well as using patterns of utilization organically. The method used in this activity is counseling, discussion with residents and the practice of making aquaponics as a model of organic yard use. The result of community service that has been done is a new understanding to the community about the importance of managing yard for agriculture and fisheries to support family food security with the availability of organic food sources in the form of vegetables and fish in their own yard. In addition, the community also knew the simple yard utilization model, namely by using the aquaponics system.